William Faulkner : Toward Yoknapatawpha and Beyond - Brooks, Cleanth, 1906-1994 (Book collections on Project MUSE., 1990)
In this companion volume to William Faulkner: The Yoknapatawpha Country, Cleanth Brooks takes an in-depth look at Faulkner's early poetry and prose as well as his five non-Yoknapatawpha novels -- Soldiers Pay, Mosquitoes, Pylon, The Wild Palms, and A Fable. Brooks also offers relevant clarification of some of his earlier interpretations of Faulkner that have been challenged -- most notably in the case of Faulkner that have been challenged -- most notable in the case of Absalom, Absalom!, which he considers Faulkner's greatest novel. Recognizing that the creative and imaginative center of F.